Traditional Chinese and Western medicine nursing of a patient after intra-aortic balloon counterpulsation (１例主动脉内球囊反搏术后患者的中西医护理) - SHI Yan (时琰); QIAN Jiali (钱佳丽); XU Wei (许卫); TAO Fang (陶芳); HANG Jianlong (杭剑龙) (Association of Integrative Nursing, 2021)
This paper reported the nursing care of a patient with acute myocardial infarction and sudden cardiac arrest undergoing interventional and aortic balloon counterpulsation. The main nursing measures included continuous ECG monitoring, balloon counterpulsation catheter observation and nursing, anticoagulation treatment, and symptomatic Chinese medicine nursing. (本文总结了1例急性心肌梗死突发心脏骤停患者行介入及主动脉球囊反搏术的护理措施。护理要点包括持续心电监护、球囊反搏导管的观察护理、抗凝治疗的护理、对症中医护理等。)